Maḥbūbuzzaman taẕkirah-yi shuʻarā-yi Dakin - ʻAbduljabbār Ḵẖāṉ, Muḥammad (SAMP early 20th-century Indian books project, 1911)
Biographical anthology of Urdu poets from Deccan; includes selection of their poems.